Direct Observation of Kinetic Pathways of Biomolecular Recognition. Issue 45 (14th September 2015) - Choudhury, Susobhan; Batabyal, Subrata; Mondal, Prasanna Kumar; Singh, Priya; Lemmens, Peter; Pal, Samir Kumar
Abstract: The pathways of molecular recognition, which is a central event in all biological processes, belong to the most important subjects of contemporary research in biomolecular science. By using fluorescence spectroscopy in a microfluidics channel, it can be determined that molecular recognition of α‐chymotrypsin in hydrous surroundings at two different pH values (3.6 and 6.3) follows two distinctly different pathways. Whereas one corroborates an induced‐fit model (pH 3.6), the other one (pH 6.3) is consistent with the selected‐fit model of biomolecular recognition. The role of massive structural perturbations of differential recognition pathways could be ruled out by earlier XRD studies, rather was consistent with the femtosecond‐resolved observation of dynamic flexibility of the protein at different pH values. At low concentrations of ligands, the selected‐fit model dominates, whereas increasing the ligand concentration leads to the induced‐fit model. From molecular modelling and experimental results, the timescale associated with the conformational flexibility of the protein plays a key role in the selection of a pathway in biomolecular recognition. Abstract : The right path : Molecular recognition of α‐chymotrypsin in hydrous surroundings at two different pH values (3.6 and 6.3) follows two distinctly different pathways. An H‐shaped microfluidics channel was used to study molecular recognition in a four‐state model (see figure).